Subsidy Landscapes and the Organizational Sociology of Scholarly Publishing - Lyall Nelson, Eric (Journal of Scholarly Publishing, 2018)
When shared among the publishers of a field, subsidies sustain the creation of varied forms of intellectual capital. The absence of subsidy regimes would likely lead to convergence around the kind of research most easily converted into financial capital. Subsidy landscapes that fail to counter the pressure to conform to market-oriented standards of organizational activity may allow such changes to happen in the nature of scholarship. Both Bourdieu and critical management studies warn us of the difficulties that can arise if we fail to see that subsidies are not only intended to balance book budgets but are also connected to a process of organizational knowledge accumulation on the part of publishers. Subsidies thus reveal the existence of publishing activities hidden from managerial views on organizations.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDkuMi4xNjY